What Has Worked? Lessons from OECD Countries to Tackle Health Inequalities: A Review of the Literature - Lkhagvasuren, Khorolsuren (Central Asian Journal of Medical Sciences, 2018)
Objectives: The main objectives of this study were to evaluate the likely effectiveness of different types of interventions available in the literature aimed at reducing socio-economic health inequalities and highlight appropriate types of interventions to tackle health inequalities for future evidence-based policy. Methods: This study systematically reviewed 26 studies to determine the impact of interventions and policies on health inequality. Key databases were searched including EBSCO, PubMed, JSTOR, Cochrane library of databases and DHS database. Results: Interventions targeting healthy behaviors and prevention were most effective at reducing health inequalities. Interventions based on education and accesses to health care services were mostly successful in reducing health inequality. Interventions on poverty reduction showed inconclusive mixed results, but were mainly unsuccessful. Conclusion: Programs based on healthy lifestyle and behaviors, better housing and safe environment and access to health care, specifically improving distribution of health professionals in remote disadvantaged areas are effective to tackle health inequalities.